Association between PTSD and Impedance Cardiogram‐based contractility metrics during trauma recall: A controlled twin study. (26th October 2022) - Sheikh, Shafa‐at Ali; Perez Alday, Erick A.; Rad, Ali Bahrami; Levantsevych, Oleksiy; Alkhalaf, Mhmtjamil; Soudan, Majd; Abdulbaki, Rami; Haffar, Ammer; Smith, Nicholas L.; Goldberg, Jack; Bremner, J. Douglas; Vaccarino, Viola; et al.
Abstract: Post‐traumatic stress disorder (PTSD) is an independent risk factor for incident heart failure, but the underlying cardiac mechanisms remained elusive. Impedance cardiography (ICG), especially when measured during stress, can help understand the underlying psychophysiological pathways linking PTSD with heart failure. We investigated the association between PTSD and ICG‐based contractility metrics (pre‐ejection period (PEP) and Heather index (HI)) using a controlled twin study design with a laboratory‐based traumatic reminder stressor. PTSD status was assessed using structured clinical interviews. We acquired synchronized electrocardiograms and ICG data while playing personalized‐trauma scripts. Using linear mixed‐effects models, we examined twins as individuals and within PTSD‐discordant pairs. We studied 137 male veterans (48 pairs, 41 unpaired singles) from Vietnam War Era with a mean (standard deviation) age of 68.5(2.5) years. HI during trauma stress was lower in the PTSD vs. non‐PTSD individuals (7.2 vs. 9.3 [ohm/s 2 ], p  = .003). PEP reactivity (trauma minus neutral) was also more negative in PTSD vs. non‐PTSD individuals (−7.4 vs. −2.0 [ms], p  = .009). The HI and PEP associations with PTSD persisted for adjusted models during trauma and reactivity, respectively. For within‐pair analysis of eight PTSD‐discordant twin pairs (out of 48 pairs), PTSD was associated with lower HI in neutral, trauma, and reactivity, whereas no association was found between PTSD and PEP. PTSD was associated with reduced HI and PEP, especially with trauma recall stress. This combination of increased sympathetic activation and decreased cardiac contractility combined may be concerning for increased heart failure risk after recurrent trauma re‐experiencing in PTSD. Abstract : Our study employed an innovative technique involving replaying scripts from previous traumas in veterans with and without post‐traumatic stress disorder (PTSD) to study the potential relationship of trauma‐induced stress and cardiac pathophysiology. This is the first investigation to examine the association of PTSD and impedance cardiogram‐based contractility metrics during a trauma recall. We found robust relationships between PTSD and worsened cardiac contractility, as well as increased sympathetic activation, particularly during trauma reminders.